Global power Europe - Vol. 1 : theoretical and institutional approaches to the EU's External Relations - Kremer, Jan-Frederik; van Loon, Aukje; Boening, Astrid (Global Power Shift, Comparative Analysis and Perspectives)
This two-volume project provides a multi-sectoral perspective over the EU's external projections from traditional as well as critical theoretical and institutional perspectives, and is supported by numerous case studies covering the whole extent of the EU's external relations. The aim is to strive to present new approaches as well as detailed background studies in analyzing the EU as a global actor. Volume 1: The first volume "Theoretical and Institutional Approaches to the EU's External Relations" addresses the EU's overall external post-Lisbon Treaty presence both globally and regionally (e.g. in its "neighborhood"), with a special emphasis on the EU's institutional framework. It also offers fresh and innovative theoretical approaches to understanding the EU's international position. -   With a preface by Alvaro de Vasoncelos (former Director European Union Institute for Security Studies)  Volume 2: The second volume "Policies, Actions and Influence of the EU's External Relations", examines in both quantitative and qualitative contributions the EU's international efficacy from a political, economic and social perspective based on a plethora of its engagements.